2021
DOI: 10.1002/aepp.13178
|View full text |Cite
|
Sign up to set email alerts
|

How will regulation influence commercial viability of autonomous equipment in US production agriculture?

Abstract: Autonomous equipment for crop production is on the brink of commercialization in the United States but federal, state, and local policies could affect commercial viability and hinder adoption. This article examines the farm‐level implications of both a speed restriction and on‐site supervisory regulations. The rules reduce the profitability of autonomous machinery, and for some scenarios autonomous machines are no longer an economically viable alternative to conventional machinery. Regulations also increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Even more cost prohibitive is the restriction that the equipment must not travel more than 2 mph. This speed restriction would make autonomous machinery uncompetitive with conventional farm machinery in most mechanized agriculture (Shockley et al, Forthcoming). Farm equipment manufacturers have tried unsuccessfully to change this California rule, but they have obtained “conditional approval” for autonomous agricultural equipment operating without human workers in the vicinity, mainly for pesticide application (Pankonin, 2019).…”
Section: Current Situation Of Regulation Of Autonomous Machines In Ag...mentioning
confidence: 99%
“…Even more cost prohibitive is the restriction that the equipment must not travel more than 2 mph. This speed restriction would make autonomous machinery uncompetitive with conventional farm machinery in most mechanized agriculture (Shockley et al, Forthcoming). Farm equipment manufacturers have tried unsuccessfully to change this California rule, but they have obtained “conditional approval” for autonomous agricultural equipment operating without human workers in the vicinity, mainly for pesticide application (Pankonin, 2019).…”
Section: Current Situation Of Regulation Of Autonomous Machines In Ag...mentioning
confidence: 99%
“…More robust and efficient perception and control methods are needed. Six, regulation and robot safety should be taken into consideration when designing and operating the robot, which can potentially increase the operation cost of the robot and limit its usages in some countries/areas [119,120].…”
Section: Rgb Cameramentioning
confidence: 99%
“…They emphasize the need for greater AI capacity if the autonomous machine is to resolve more issues without human intervention. Shockley et al (2021) extended the earlier Kentucky analysis to consider the economic impact of autonomous machine speed restrictions and found that, for maize and soybean farms, these can make the machines unprofitable.…”
Section: Autonomous Crop Machinesmentioning
confidence: 99%
“…Under some ISO standards, autonomous machine categories are limited to less than 0.8 kilometres per hour. Shockley et al (2021) show that applying such speed limits generally in crop farming would undercut the economic benefit of autonomous machinery.…”
Section: Policy Regulatory and Institutional Issuesmentioning
confidence: 99%